Montmorillonite (MMT) nanoclay in smart coatings for corrosion protection of metal alloy - N., Affaf; J., Alias; Nasrul Azuan, Alang (IOP Publishing, 2024)
Montmorillonite (MMT) nanoclay is a natural raw material naturally occurring 2-dimensional lamellar silicate material. Many advantages of MMT clay are low cost, high dispersion properties, good mechanical properties, hydrophobic, good shield against corrosive media, non-toxic, easily accessible, and most importantly, it is natural. MMT was mainly used as an additive with other active smart materials to enhance the excellent properties for smart coatings. However, there is not much research done from the last 5 years regarding MMT in smart coating for corrosion protection. The discussion regarding MMT for corrosion protection is also contradict between each research. This paper provides a brief review on MMT clay in smart coatings and its advantages for corrosion protection for the last 5 years. There are also some drawbacks of MMT in smart coatings discussed at the end. Further research needs to be done as MMT has more potential that can be used in the real-world industries and to clarify the contradiction of statement existed in much research.